Modality and Perceptual-Motor Experience Influence the Detection of Temporal Deviations in Tap Dance Sequences - Murgia, Mauro; Prpic, Valter; O, Jenny; McCullagh, Penny; Santoro, Ilaria; Galmonte, Alessandra; Agostini, Tiziano (Frontiers in Psychology, 2017)
Accurate temporal information processing is critically important in many motor activities within disciplines such as dance, music, and sport. However, it is still unclear how temporal information related to biological motion is processed by expert and non-expert performers. It is well-known that the auditory modality dominates the visual modality in processing temporal information of simple stimuli, and that experts outperform non-experts in biological motion perception. In the present study we combined these two areas of research; we investigated how experts and non-experts detected temporal deviations in tap dance sequences, in the auditory- compared to the visual-modality. We found that temporal deviations were better detected in the auditory modality compared to the visual modality, and by experts compared to non-experts. However, post-hoc analyses indicated that these effects were mainly due to performances obtained by experts in the auditory modality. The results suggest that the experience advantage is not equally distributed across the modalities, and that tap dance experience enhances the effectiveness of the auditory- but not the visual-modality when processing temporal information. The present results and their potential implications are discussed in both temporal information processing and biological motion perception frameworks.